Village Fund Management: An Analysis of Human Resource Quality, Village Apparatus, and Internal Control System - Jaenudin, Ujang Eri; Ridwan, Rizky; Rachmanda, Yudi Setia (Universitas Islam Kadiri, 2025)
This study aims to analyze the influence of human resource quality, the role of village officials, and internal control systems on the accountability of Village Fund management. The main issue underlying this research is the low level of accountability in village financial management, which affects transparency and public trust. This study employs a quantitative approach with a sample of 75 respondents consisting of village officials and youth organization members in Sukamanah Village. Data were collected through an online questionnaire and analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method with the assistance of SmartPLS software. The results indicate that all three independent variables human resource quality, the role of village officials, and internal control systems have a positive and significant influence on the accountability of Village Fund management. These findings highlight that strengthening the capacity of village officials and implementing an effective internal control system are strategic steps in establishing transparent and sustainable village financial governance. This research is expected to provide useful insights for village governments and other stakeholders in efforts to improve the accountability of Village Fund management